Design and implementation of a real-time wireless sensor network - Afonso, José A. (2007)
This paper describes the development of wireless sensor network prototype that gathers biometrical data and posture information from several wearable sensor networks and sends it in real-time to a personal computer where the information is monitored and stored. The wireless sensor network is based on a low power real-time MAC protocol that was designed and implemented in the MICAz platform. This paper also presents some analytical results and several experimental results regarding the behavior of the developed system.